JURIDICAL ANALYSIS OF APPEAL COURT DECISION NUMBER: 330/PDT/2023/PT BDG ON INDEMNIFICATION - Hidayat, Ahmad; Hartantien, Sinarianda Kurnia; Kumalasari, Dewi Ratih; Deviyanti, Charina Ayu (jfpublisher, 2024)
Globalization and the development of information technology, especially the internet, have changed many aspects of human life, which includes the way people connect with each other. Easy access to new information and social media usage, such as Facebook, create new legal challenges, especially when it comes to defamation. In Indonesia, the ITE Law regulates online behavior related to defamation, and Articles 1365 and 1372 of the Civil Code allow victims to claim damages, both physical and psychological, for losses suffered. This research aims to understand that defamation can be categorized as a violation of the law and punitive damages can be claimed. This normative juridical research uses primary legal materials, such as the Civil Code, Criminal Code, and Electronic Information Technology Law, as with secondary legal materials such as literature and journals. Articles 1365-1380 of the Civil Code regulate unlawful acts that can damage a person’s reputation. For instance, the case of Iin Yuhinda v. Septiano Broery Hidayat shows that defamation is a tort if it fulfills the elements in Article 1365 of the Civil Code. In addition, Articles 1243-1252 of the Civil Code also regulate compensation in violation of law cases. The results of this research indicated that a person who is damaged by defamation has the right to file a claim for compensation because it violates the law. Article 1365 of the Civil Code states that any act that harms another person must be compensated, while Articles 1372-1380 regulate the manner of claiming compensation for defamation.